The power of biomass: Experts disclose the potential for success of bioenergy technologies - Giulia Fiorese; Michela Catenacci; Valentina Bosetti; Elena Verdolini (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper focuses on technologies which use thermo-chemical or biochemical processes to convert biomass into electricity. We present the results from an expert elicitation exercise involving sixteen leading experts coming from different EU Member States. Aim of the elicitation was to assess the potential cost reduction of RD&D (Research, Development and Demonstration) efforts and to identify barriers to the diffusion of these technologies. The research sheds light on the future potential of bioenergy technologies both in OECD (Organisation for Economic Co-operation and Development) and non-OECD countries. The results we present are an important input both for the integrated assessment modeling community and for policy makers who draft public RD&D strategies.
Keywords: Q42; Q55; 330; expert elicitation; research; development and demonstration; bioenergy